Truncal blocks and teenager postoperative pain perception after laparoscopic surgical procedures. (July 2019) - Visoiu, Mihaela; Chelly, Jacques; Kenkre, Tanya
Abstract: Introduction: The prevalence of moderate to severe pain is high in hospitalized teenage patients admitted to surgical services. Objectives: The aims of this study were to determine (1) the preoperative and postoperative factors influencing teenager postoperative pain perception; and (2) suffering, defined as the patient's anxiety, pain catastrophizing thoughts, and mood. Methods: Data were collected from medical records and from 2 medical interviews at the time of enrollment and postoperative day 1. Stepwise linear regression was conducted to assess variables that predicted teenagers' pain scores and suffering. Results: Two hundred two patients (mean age = 13.8 years, SD = 1.9), 56.4% females, scheduled for laparoscopic surgical procedures completed the study. The variables found to be significant predictors of pain response in teenagers were pain on the day of surgery (6.81, 95% confidence interval [CI] = 0.08–13.55, P = 0.05) and use of regional anesthesia (single-injection rectus sheath, transversus abdominis plane, and paravertebral nerve blocks) (−6.58, 95% CI = −12.87 to −0.30, P = 0.04). The use of regional anesthesia was found to predict mood responses (all patients: 2.60, 95% CI = 0.68–4.52, P = 0.01; girls: 3.45, 95% CI = 0.96–5.93, P = 0.01; 14–17-year-old teens: 2.77, 95% CI = 0.44–5.10, P = 0.02) and to negatively predict catastrophic thoughts among all patients as a group (−4.35, 95% CI = −7.51 to −1.19, P = 0.01) and among 14- to 17-year-old teens (−5.17, 95% CI = −9.44 to −0.90, P = 0.02). Conclusion: A comprehensive pain approach that includes truncal blocks may improve teenagers' postoperative pain control after laparoscopic surgeries.